Comparison of Postoperative Anatomy Using Anatomic Total Shoulder Arthroplasty Versus Soft-Tissue Balancing Total Shoulder Arthroplasty. Issue 19 (1st October 2021) - Truntzer, Jeremy; Vopat, Bryan; Schwartz, Joel; Anavian, Jack; Barnds, Brandon L.; Blaine, Theodore A.; Green, Andrew
Abstract : Background: The importance of anatomic reconstruction of the proximal humerus on shoulder biomechanics and kinematics after anatomic total shoulder replacement (aTSR) has been highlighted by a number of investigations. The humeral head designs of current-generation shoulder arthroplasty emphasize either anatomic or soft-tissue balancing total shoulder arthroplasty (sbTSR) philosophies. The purpose of this study was to compare the postoperative anatomy of TSR systems used to treat primary glenohumeral osteoarthritis. Methods: This was a matched cohort study of 60 patients treated with either press-fit aTSR or sbTSR by two shoulder surgeons. The analysis of postoperative true AP radiographs was performed to calculate multiple representative anatomic parameters of the TSR. Results: A significant difference was observed in the average measurements between the sbTSR and aTSR designs about the humeral head center offset (5.2 ± 0.4 mm versus 3.9 ± 0.3 mm; P = 0.02), implant–humeral shaft angle (0.3 ± 0.3 varus versus 1.7 ± 0.3 valgus, P < 0.001), and humeral head to tuberosity height (8.8 ± 0.4 mm versus 6.2 ± 0.4, P < 0.001), respectively. No significant difference was observed in the average measurements between the two systems' designs regarding the head–shaft angle (133.4 ° ± 0.8 ° versus 135.0 ° ± 1.0 °, P = 0.16) and the relation of humeral head to lateral humeral cortex (0.15 ± 0.6 mm inside the lateral cortex versus 0.19 ± 0.6 outside the lateral cortex; P = 0.69), respectively. Conclusions: Despite differing design philosophies of these systems, and some notable differences, the absolute differences between the measured anatomic parameters were small and not likely clinically relevant. Anatomic and soft-tissue balancing humeral arthroplasty implants can both reliably reconstruct proximal humeral anatomy.